Eksistensi Tauhid Dalam Pemikiran Pendidikan Islam - M Riza Zainuddin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2016)
The teaching of unity is spirit in Islamic education. When the man reached the height of science and then he should be aware that all for reaching wisdom in deeds, words and thoughts as god expects. When delivering the human science to spiritual superficiality, reducing the quality of love for our god (Alloh) and his prophet. For example, he was on the wrong way, hence the need to reconceptualized the Islamic concept of Alloh, the concept of an enduring stability and changed of the value.